Penguatan Religiusitas Peserta Didik Melalui Kajian Kitab Uyunul Masa-Il Lin Nisa di SMP Islam Al-Azhar Kediri - Yulia Wulandari; Mohammad Turmudi; Hamam Syamsuri (STIKes Ibnu Sina Ajibarang, 2025)
In general, in-depth study of women's fiqh is still limited to the introduction and has not been deeply conveyed in the family environment, as well as during fiqh lessons in class is still limited to the introduction, this is due to the limited time given by the school. Coupled with an environment that does not support the study of women's fiqh. The aim of this research is to find out: (1) What is the process learning of the book Uyunul Masa-il Lin Nisa at Al-Azhar Islamic Middle School, Kediri? (2) How is the evaluation of learning about the study of the book Uyunul Masa-il Lin Nisa in strengthening the religiosity of students at Al-Azhar Islamic Middle School Kediri? This research is research using a qualitative approach and descriptive research type. Data collection techniques use observation, interviews and documentation. Meanwhile, data analysis techniques include; data reduction, data presentation, and drawing conclusions. The results of the research are: (1) The process learning of the book Uyunul Masa-il Lin Nisa starting from the learning methods chosen include discussion, lecture and question and answer methods as well as the subject matter presented. (2) In evaluation, teachers use evaluation models in oral and written form. Teachers assess students' understanding of the concepts in the Uyunul Masa-il Lin Nisa book, practical assignments given by subject teachers and students' ability to apply these teachings in everyday life as well as students' skills in compiling and conveying thoughts. related to the book.